2021
DOI: 10.3389/fphar.2021.645354
|View full text |Cite
|
Sign up to set email alerts
|

Yanghe Decoction Suppresses the Experimental Autoimmune Thyroiditis in Rats by Improving NLRP3 Inflammasome and Immune Dysregulation

Abstract: Inflammation is an important contributor to autoimmune thyroiditis. Yanghe decoction (YH) is a traditional Chinese herbal formulation which has various anti-inflammatory effects. It has been used for the treatment of autoimmune diseases such as ankylosing spondylitis In this study we aimed to investigate the effects of YH on autoimmune thyroiditis in a rat model and elucidate the underlying mechanisms. The experimental autoimmune thyroiditis (EAT) model was established by thyroglobulin (pTG) injections and exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 47 publications
(53 reference statements)
2
9
0
Order By: Relevance
“…Therefore, 10 g crude herbs/kg is almost equivalent to the human therapeutic dose, 5 g crude herbs/kg and 20 g crude herbs/kg are almost 0.5-fold and 2-fold of the human therapeutic dose, respectively. The doses of MGQD extract used in mice in this study were also consistent with that in most previous studies, that is, the dosage of decoction in rodents reached crude drug g/kg/d (Luo et al, 2019;Ma et al, 2021;Song et al, 2021). However, the standardization of bioactive compounds in MGQD and future studies at lower doses levels to evaluate the anti-UC potential of MGQD decoction are worthy of further exploration.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, 10 g crude herbs/kg is almost equivalent to the human therapeutic dose, 5 g crude herbs/kg and 20 g crude herbs/kg are almost 0.5-fold and 2-fold of the human therapeutic dose, respectively. The doses of MGQD extract used in mice in this study were also consistent with that in most previous studies, that is, the dosage of decoction in rodents reached crude drug g/kg/d (Luo et al, 2019;Ma et al, 2021;Song et al, 2021). However, the standardization of bioactive compounds in MGQD and future studies at lower doses levels to evaluate the anti-UC potential of MGQD decoction are worthy of further exploration.…”
Section: Discussionsupporting
confidence: 90%
“…The main components of Yanghe Decoction include Rehmannia glutinosa, Colla Cornus Cervi, Cinnamomum cassia, Ephedra sinica, Semen Sinapis, Rhizoma Zingiberis Preparata, and Glycyrrhiza. Yanghe Decoction has been proved to play a significant antiinflammatory role in disease treatment through the NLRP3 inflammatory inflammasome [ 11 ], as well as JAK/STAT [ 12 ] and Wnt/ β -catenin [ 13 ] pathways. It is worth noting that Yanghe Decoction has great potential therapeutic value in asthma treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The extraction rate of 21.261% was obtained by evaporation of the concentrate at 100 °C. These doses used in this study were within the range of in vivo studies reported by others (Luo et al, 2019;Lin et al, 2020;Ma et al, 2021;Song et al, 2021).…”
Section: Introductionsupporting
confidence: 61%